A soluble DR5‐Fc chimeric protein attenuates inflammatory responses induced by coronavirus MHV‐A59 and SARS‐CoV‐2. Issue 11 (5th August 2022) - Peng, Hong; Zheng, Birong; Yang, Sidi; Du, Jie; Cao, Liu; Liu, Lihong; Ma, Zengyi; Wu, Junyu; Li, Chunmei; Zhang, Hailong; Guo, Deyin
Abstract: Mortality in coronavirus disease 2019 (COVID‐19) patients has been linked to the presence of a "cytokine storm" induced by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, which involves elevated levels of circulating cytokines and immune‐cell hyperactivation. Targeting cytokines during the management of COVID‐19 patients has the potential to improve survival rates and reduce mortality. Although cytokine blockers and immune‐host modulators are currently being tested in severely ill COVID‐19 patients to cope with the overwhelming systemic inflammation, there is not too many successful cases, thus finding new cytokine blockers to attenuate the cytokine storm syndrome is meaningful. In this paper, we significantly attenuated the inflammatory responses induced by mouse hepatitis viruses A59 and SARS‐CoV‐2 through a soluble DR5‐Fc (sDR5‐Fc) chimeric protein that blocked the TNF‐related apoptosis‐inducing ligand–death receptor 5 (TRAIL–DR5) interaction. Our findings indicates that blocking the TRAIL–DR5 pathway through the sDR5‐Fc chimeric protein is a promising strategy to treat COVID‐19 severe patients requiring intensive care unit  admission or with chronic metabolic diseases.